1985
DOI: 10.1121/1.391704
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave excitation in unconsolidated ocean sediments

Abstract: Fo values was considered. The second describes the contours as the output of two second-order systems, one for sentence phrasing (whose excitation pulses are related to the sentence structure) and one for syllable emphasis. Masking levels for maskers consisting of harmonic complex tones structured in time and frequency (in German) [43.66.Dc, 43.66.Fe, 43.66.Nm, 43.66.Mk, 43.66.Ki]--Henning Alphei, Drittes Physikalisches Institut, Universiti•t Gbttingen, Fed. Rep. Germany, Sept. 1984 (Dipl.--Phys.) Masked thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some of the experimental results [e.g., Ingenito and Wolf (1976), McDaniel and Beebe (1980), Chapman and Ellis (1984), Beebe and Holland (1986), Hughes et al (1990)], however, indicated that the effect of the sediment rigidity could be significant for various environments. Modeling efforts [Fryer (1978), Vidmar (1980), Holland (1985)] that considered the sediments as viscoelastic attempted to determine the bounds of validity for the fluid approximation as a function of frequency and seafloor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the experimental results [e.g., Ingenito and Wolf (1976), McDaniel and Beebe (1980), Chapman and Ellis (1984), Beebe and Holland (1986), Hughes et al (1990)], however, indicated that the effect of the sediment rigidity could be significant for various environments. Modeling efforts [Fryer (1978), Vidmar (1980), Holland (1985)] that considered the sediments as viscoelastic attempted to determine the bounds of validity for the fluid approximation as a function of frequency and seafloor environment.…”
Section: Introductionmentioning
confidence: 99%